Dampak Alih Fungsi Lahan Karet Menjadi Lahan Kelapa Sawit terhadap Ekonomi Petani di Kecamatan Sungai Gelam - Fajar Romadon; Zulgani Zulgani; Nurhayani Nurhayani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This research aims to analyze: (1) the general characteristics of farmers who convert rubber land to oil palm plantations in Sungai Gelam District, and (2) the economic impact of this land conversion, particularly on farmers’ income. This study uses a quantitative approach with survey data collected from rubber and oil palm farmers. The results show that there are notable differences in farmer characteristics, including capital, labor use, and market access. The average income difference between rubber and oil palm farmers is IDR 2,712,000, indicating higher earnings from oil palm cultivation. Based on the BNT test, with a value of IDR 405,000, the average income difference exceeds the threshold, confirming that the difference is statistically significant. Furthermore, the calculated F value is greater than the F table value, which strengthens the conclusion that there is a significant difference in income between rubber and oil palm farmers. Therefore, land conversion contributes positively to farmers’ income improvement.